Density, dimensions and depth of stomata in the needles of Pinus nigra in polluted and in clean environment - Jordanov, Saško; Gudeski, Atanas (Macedonian Journal of Ecology and Environment, 2003)
The research was conducted in 1993, on 2 years old needles of the Pinus nigra Arn. (black pine) in polluted areas (Aerodrom, Cair and Panorama, Skopje, Republic of Macedonia) and clean environment areas (Treska, Golak and Ablanica). The work presents the data of the analysis of the stomatal apparatus on the face and back side of the needles. For the purpose of the stomatal apparatus analysis, semi-permanent glycerine slides were made of the face and back side of the needles. The number of stomata per mm2 and their dimensions in ìm were studied on length section (macerated), while the depth of stomata in ìm on a cross section. Slides were analysed on enlargements of 50-1000x prepared according to the standard methods.